Responsibility in world business : managing harmful side-effects of corporate activity - Bomann-Larsen, Lene; Wiggen, Oddny (United Nations University Press, 2004)
How should companies deal with the harmful side-effects of their business operations? To what extent should they be held responsible for the wrongdoing of other actors? And how can they conduct business in a responsible manner in countries where human rights abuses are widespread, or where the environment is being degraded? These are crucial issues within the current debate on corporate responsibility and they represent the most substantial challenges confronting the business community today. This book offers an approach to corporate decision-making based on the principles of Just War Theory, primarily the Principle of Double Effect (PDE). The proposed normative framework can be used both as a tool for performance evaluation, and as a set of guidelines for conducting business in an ethically responsible manner. Multiple case studies illustrate the usefulness of incorporating the Principle of Double Effect into corporate decision-making, and show how the proposed framework can help companies assume responsibility for the impact of their operations on multiple stakeholders.